Comparison of the Inhibitory Binding Modes Between the Planar Fascaplysin and Its Nonplanar Tetrahydro-β-carboline Analogs in CDK4 - Liang, Yan; Quan, Huili; Bu, Tong; Li, Xuedong; Liu, Xingang; Wang, Songsong; He, Dian; Jia, Qingzhong; Zhang, Yang (Frontiers in Chemistry, 2021)
Fascaplysin is a natural marine product originating from sponges, attracting widespread attention due to its potential inhibitory activities against CDK4. However, its clinical application has been largely limited because of serious adverse effects caused by planar skeleton. To reduce the serious adverse effects, three tetrahydro-β-carboline analogs (Compound 6a, 6b, and 6c) were designed and synthesized via breaking the planarity of fascaplysin, and the biological activities of the synthesized compounds were evaluated by MTT assay and CDK4/CycD3 enzyme inhibition assay. The title compounds showed comparable inhibitory activities compared to fascaplysin, especially the cytotoxicity of Compound 6c against Hela cells (IC50 = 1.03±0.19 μM) with quite weak cytotoxicity towards the normal cells WI-38 (IC50 = 311.51±56.06 μM), and the kinase inhibition test indicated that Compound 6c was a potential CDK4 inhibitor. In order to further compare the action mechanisms of planar and non-planar molecules on CDK4, the studied complexes of CDK4 bound with fascaplysin and the tittle compounds were constructed by molecular docking, and further verified through molecular dynamic simulation, which identified the key residues contributing the ligands’ binding. By comparing the binding modes of the constructed systems, it could be found that the residues contributing significantly to Compound 6c’s binding were highly consistent with those to fascaplysin’s binding. Through the design, synthesis of the non-planar fascaplysin derivatives and binding mechanism analysis, some valuable hints for the discovery of anti-tumor drug candidates could be provided.